Homesickness pada Santri Baru: Kontribusi Kecerdasan Emosi dan Teman Sebaya - Aulia, Lailatuzzahro Al-akhda; Ma’rufah, Faidatul (Sultan Idris Journal of Psychology and Education, 2025)
Teenagers who move from their home to Islamic boarding schools causes separation from their families and surrounding environment, which can make them feel depressed. One of the negative reactions that arise from separation with families is homesickness. This study was conducted to examine the influence of emotional intelligence and peer social support on homesickness. Participants in this study were new students were 85 students, who were selected by accidental sampling. Data in this study were collected used homesickness scale, emotional intelligence scale, and peer social support scale. The reliability coefficient are 0.801 for homesickness scale, 0.672 for emotional intelligence scale, and 0.803 for peer support scale Hypothesis testing was conducted using regression analysis with 2 predictors, obtaining F value = 3.306 with p = 0.000 (p < 0.05). The results of this study indicate that emotional intelligence and peer social support influenced homesickness among new students. Furthermore, the partial correlation results showed that emotional intelligence was not correlated with homesickness, but peer social support was significantly correlated with homesickness.